1996
DOI: 10.1115/1.2822670
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Spacing Between Pin Fins With Impinging Flow

Abstract: This is an experimental numerical and theoretical study of the heat transfer on a pin-finned plate exposed to an impinging air stream. The pin fins are aligned with the air approach velocity. The base plate and the fin cross section are square. It is demonstrated experimentally that the thermal conductance between the plate and the air stream can be maximized by selecting the fin-to-fin spacing S. Next, a simplified numerical model is used to generate a large number of optimal spacing and maximum heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Similar studies for forced convection were performed by Nakayama et al [8] and Bejan and Sciubba [9]. Ledezma et al [10] demonstrated the existence of an optimal spacing between pin fins in crossflow and impinging flow. Based on theoretical arguments relating to similarity of flow and heat transfer, the form of the correlation was borrowed from previous studies on cross-flow over staggered cylinders [7] and flow between parallel plates [9].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Similar studies for forced convection were performed by Nakayama et al [8] and Bejan and Sciubba [9]. Ledezma et al [10] demonstrated the existence of an optimal spacing between pin fins in crossflow and impinging flow. Based on theoretical arguments relating to similarity of flow and heat transfer, the form of the correlation was borrowed from previous studies on cross-flow over staggered cylinders [7] and flow between parallel plates [9].…”
Section: Introductionsupporting
confidence: 54%
“…Problem parameters, such as base and fin dimensions and flow speeds, are matched with Ref. [10]. The OUU framework developed here is verified against simple analytical and 2D problems, such as flow in a channel with uncertain viscosity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimum amount of heat transfer occurs at r/D=1.3 and the second peak heat transfer at r/D=1.8. Ledezma et al [4] numerically and experimentally investigated heat transfer in finned plate with impinging flow. They found an equation for optimum fin distances and the maximum thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%